Absence of and options for investor-state dispute settlement mechanisms in regional comprehensive economic partnership agreements - Chen, Zhengrong; Ab Rahman, Suhaimi; Khan, Hanna Ambaras (Human Resources Management Academic Research Society (HRMARS), 2023)
The RCEP dispute settlement mechanism lacks an investor-state dispute settlement mechanism, which will result in the limitation of low level of entity protection in the field of investment.The Regional Comprehensive Economic Partnership Agreement (RCEP) came into force on January 1, 2022.Chapter 19 of the RCEP agreement provides for a separate dispute settlement provision, showing the importance of the RCEP agreement to dispute settlement, but with the further entry into force of the level of regional cooperation However, as the level of regional cooperation further takes effect, the gradually expanding level of investment will require a more sound mechanism for remedy and protection of investment rights, for which the RCEP is incomplete without an investor-state dispute settlement mechanism, and the subsequent negotiations of the RCEP can follow the existing mechanism of the RCEP, invoke other international investor dispute mechanisms, and establish the RCEP's own investment tribunal to resolve investor-state disputes. In order to seek to form a multi-modality investor dispute settlement mechanism that integrates dispute prevention, consultation, mediation or arbitration.